The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/tmi.12787
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor expressed on myeloid cells 1 (TREM‐1) and cytokine gene variants in complicated and uncomplicated malaria

Abstract: Higher plasma levels of sTREM-1 alone or relative to sTREML-1 during malaria predispose to the phenotype of severe malaria. Carriage of the TREM1 rs2234237T allele appears to be a risk factor for the development of severe malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
1
21
0
2
Order By: Relevance
“…However, our analyses provided hints that certain pathways may be shared, including TREM-1 activation, as well as "alternative activation" pathways similar to M2 alternatively activated macrophages in mice. In malaria, TREM-1 has been described to have a role in severe disease outcomes (79). We have also identified cytokines like OSM and TNFSF14 (LIGHT) that seem to be expressed in human primary DC activation states that lack expression of typical inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 79%
“…However, our analyses provided hints that certain pathways may be shared, including TREM-1 activation, as well as "alternative activation" pathways similar to M2 alternatively activated macrophages in mice. In malaria, TREM-1 has been described to have a role in severe disease outcomes (79). We have also identified cytokines like OSM and TNFSF14 (LIGHT) that seem to be expressed in human primary DC activation states that lack expression of typical inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 79%
“…Another plausible explanation could be attributed to the host genetic factors, as donor-to-donor variations were observed in our study. Gene polymorphisms within TREM-1 have been linked to the development of inflammation and sepsis 54 , and it has been reported that there is a positive association between patients carrying the TREM-1 rs2234237T allele and the development of severe malaria, due to the presence of higher levels of soluble TREM-1 in the plasma of these patients 55 . Given that polymorphisms in EV-A71 receptors, scavenger receptor class B member 2 (SCARB2) and P-selectin glycoprotein ligand-1 (PSGL-1), have been shown to affect EV-A71 susceptibility and infection respectively 56 , genomic variations within TREM-1 could also play a probable role in modulating EV-A71 infection and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible explanation could be attributed to the host genetic factors, as donor-to-donor variations were observed in our study. Gene polymorphisms within TREM-1 have been linked to the development of inflammation and sepsis (44), and it has been reported that there is a positive association between patients carrying the TREM-1 rs2234237T allele and the development of severe malaria, due to the presence of higher levels of soluble TREM-1 in the plasma of these patients (45). Given that polymorphisms in EV71 receptors, scavenger receptor class B member 2 (SCARB2) and P-selectin glycoprotein ligand-1 (PSGL-1), have been shown to affect EV71 susceptibility and infection respectively (46), genomic variations within TREM-1 could also therefore play a role in modulating EV71 infection and outcomes.…”
Section: Discussionmentioning
confidence: 99%